IT Governance Design Based on COBIT 2019 SME Focus Area for UMKM BPRBCo Digital Transformation - Andika, Dafa; Mulyana, Rahmat; Ramadhani, Luthfi (Journal of Information System Research (JOSH), 2024)
Along with the industrial revolution 4.0, incumbent organizations such as BPRBCo need to carry out Digital Transformation (DT) to stay relevant. However, many DT failures are suspected to be caused by suboptimal IT Governance (ITG). Previous research has shown the importance of ambidextrous ITG (traditional and agile hybrid) for large banks with the use of the COBIT 2019 framework that focuses on IT services, information security, and DevOps. However, this approach has not been proven to also apply to small banks. Therefore, this study aims to compile and design recommendations for priority ITG solutions for SME-scale organizations and estimate the increase in maturity level capabilities to support DT success. This study uses five stages of Design Science Research (DSR), namely problem identification, requirements specification, design and development, demonstration, and evaluation. Data was collected through semi-structured interviews and documents triangulation, then analyzed using the SME focus area of COBIT 2019. Based on the priority analysis based on design factors and previous studies, 3 prioritized ITG objectives were found, namely EDM03 Ensured Risk Optimization, MEA03 Managed Compliance with External Requirements, and DSS01 Managed Operations with an average capability maturity level of 3.3. Based on the findings of these gaps, 5 essential solutions were recommended and designed based on 7 ITGM components. These recommendations were then compiled into an implementation roadmap as a priority reference for BPRBCo which is expected to increase its capability to 3.5 if implemented properly. This study contributes to the ITG knowledge base for DT in small banks as a case study of SMEs and provides practical implications for the management of similar organizations.